GP Ansor Communication Strategy in Increasing Awareness Following The Organization - Tri Wijianto; Turhamun (IQTIDA : Journal of Da'wah and Communication, 2022)
The Ansor Youth Movement is one of the largest youth organizations in Indonesia under the auspices of Nahdlatul Ulama, starting from the central, branch, and branch levels. GP Ansor of Pagubugan Kulon has a very important contribution to society in the religious and social fields. In addition, GP Ansor is said to be the most active youth organization in the village of Pagubugan Kulon because through its work program it can attract people to join the organization. This is evidenced by the increase in the number of members from only 2 in 2016 to 40 to date, consisting of 18 official members through PKD (Basic Leadership Training) and 22 active and unofficial members. For this reason, this study aims to determine the communication strategy carried out by GP Ansor of Pagubugan Kulon in increasing awareness of joining the organization.In this study, researchers conducted qualitative research using case studies that can be used to analyze personal life, history, behavior, organizational functionalization, social development, or family relationships. After doing the research, the researchers found that GP Ansor of Pagubugan Kulon used the communication strategy theory, namely the selection of communicators, setting targets, compiling information/messages, and selecting media. The preparation of targets and messages is carried out by the management and members before carrying out the activity program by holding face-to-face meetings, the media used by GP Ansor include Facebook, Youtube, Twitter, and Instagram. However, of the media that has the most influence is Facebook. Then, the theory of consciousness found in this study is the theory of Zeman which divides it into 3 main points of consciousness, namely, a) awareness in a waking state, namely the desire of the community to interact and communicate more broadly through GP Ansor, b) awareness as an experience, namely the desire of the community. participate and become part of the organization at this time, c) awareness as a mind, namely the hopes and beliefs of the community to participate in joining the GP Ansor Ranting Pagubugan Kulon organization.